(3efJNH UhGf GdMceIs - (3eLghds; (3GdSLRj , WGgQ Hf EHQGgje Hf eMeO Hf WGgQ GdSLRj, CHh GdMSjfs ((3CHhGdMSf Ydj Gdehab Hf GdeJWdH s)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf MeO GdTGcQjf s
(3de jYde efJNHg ZjQ Cfg cGf JdejPkG eYGUQkG dTgGH GdOjf GdSgQhQOi GdebJhd HMdH SfI (B587 (3ceG aj JQLeJgs
(3GdPi Cdag ai JGQjN GdMceGA hGdadGSaI CHh eMeO Hf WGgQ Hf HgQGe GdSLRi ef YdeGA BNQ GdeGFI GdQGHYIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
(3GNJjGQs
Keywords: (3GdJGQjNs